2023
DOI: 10.3390/bios13030398
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Biosensing and Diagnostic Methods for Novel Cancer Biomarkers

Abstract: Cancer is one of the major public health issues in the world. It has become the second leading cause of death, with approximately 75% of cancer deaths transpiring in low- or middle-income countries. It causes a heavy global economic cost estimated at more than a trillion dollars per year. The most common cancers are breast, colon, rectum, prostate, and lung cancers. Many of these cancers can be treated effectively and cured if detected at the primary stage. Nowadays, around 50% of cancers are detected at late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 239 publications
0
7
0
Order By: Relevance
“…Therefore, correct identification and workup is essential. Especially given that the diagnosis of MC is challenging and can be confused with the diagnosis of other histological subtypes of colon MC, which necessitate a comprehensive pathological examination, in addition to immunohistochemical staining, to confirm the diagnosis of medullary adenocarcinoma of the colon [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, correct identification and workup is essential. Especially given that the diagnosis of MC is challenging and can be confused with the diagnosis of other histological subtypes of colon MC, which necessitate a comprehensive pathological examination, in addition to immunohistochemical staining, to confirm the diagnosis of medullary adenocarcinoma of the colon [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, although patients are diagnosed with TC by ultrasound, other molecular markers are still needed to improve the accuracy of diagnosis. A study suggested that, because elevated serum thyroglobulin (Tg) can be seen in patients with benign thyroid disease, the measurement of Tg is helpful to determine the prognosis of patients receiving differentiated TC treatment [ 27 ]. However, Haugen, B.R., et al, d id not recommend to assess the prognosis of patients undergoing thyroidectomy using Tg level only, as elevated Tg might also be a manifestation of the development of other cancers [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is the predominant subtype of pancreatic cancer, characterized by a 5-year survival rate of under 10%. This poor prognosis is partially attributed to the diagnosis of most cases at advanced stages, resulting from a scarcity of early symptoms and the lack of effective early detection strategies [ 3 , 4 ]. Multiple treatment strategies, including the combination cytotoxic chemotherapy and recent targeted therapies, have been utilized for pancreatic cancer management in recent years.…”
Section: Introductionmentioning
confidence: 99%